2011
DOI: 10.1002/cncr.25960
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma with extrahepatic metastasis

Abstract: BACKGROUND: Despite significant advances in the treatment of intrahepatic lesions, the prognosis for patients with hepatocellular carcinoma (HCC) who have extrahepatic metastasis remains poor. The objective of this study was to further elucidate the clinical course and prognostic determinants of patients with this disease. METHODS: In total, 342 patients who had HCC with extrahepatic metastasis were enrolled. The metastases were diagnosed at initial presentation with HCC in 28 patients and during follow-up in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
331
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 383 publications
(357 citation statements)
references
References 43 publications
20
331
6
Order By: Relevance
“…As regards clinical characteristics, including main site of metastasis and survival, our results were similar to those of previous reports (17)(18)(19)(20)(21)(22). The analysis of prognosis revealed that the degree of intrahepatic tumor progression (T stage), hepatic functional reserve (Child-Pugh class) and tumor marker levels (AFP) were all significant prognostic factors, as previously reported (19,21,22).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As regards clinical characteristics, including main site of metastasis and survival, our results were similar to those of previous reports (17)(18)(19)(20)(21)(22). The analysis of prognosis revealed that the degree of intrahepatic tumor progression (T stage), hepatic functional reserve (Child-Pugh class) and tumor marker levels (AFP) were all significant prognostic factors, as previously reported (19,21,22).…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that common sites of extrahepatic metastasis that are clinically characteristic for this stage of HCC in patients aged >50 years include the lungs (39.5-67.3%), followed by the lymph nodes (27.9-45.0%) and bone (18.3-35.8%) (17)(18)(19)(20)(21)(22). As regards prognosis, the MST has been reported to be 4.9-8.1 months (19,20,22) whereas survival analyses indicate that the state of the intrahepatic tumor, Child-Pugh class and tumor markers are independent prognostic factors of survival (19,20,23). The analysis of stage IVB HCC prognosis indicates that there are more deaths from intrahepatic events rather than from extrahepatic events, and the degree of intrahepatic tumor progression is a significant risk factor (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for this lack of difference is that worse liver function and an increased malignant potential of previously treated patients may offset the more advanced stage of intrahepatic tumors of previously untreated patients. The major sites of HCC metastasis included the lungs, lymph nodes, bones and adrenal glands (13,14,(19)(20)(21). Yoo et al (20) reported that the most frequent metastatic sites in 251 previously untreated HCC patients with extrahepatic metastasis were the lungs (67.3%), lymph nodes (37.5%), bones (18.3%) and adrenal glands (7.6%).…”
Section: Discussionmentioning
confidence: 99%
“…As regards patients with advanced HCC with extrahepatic metastasis, several previous studies only reported the clinicopathological characteristics and prognosis of patients with HCC recurrence or a combined set of previously treated and untreated patients (11)(12)(13)(14) …”
Section: Introductionmentioning
confidence: 99%